Postmaterialism and young people's political participation in a time of austerity1. (30th August 2017) - Henn, Matt; Oldfield, Ben; Hart, James
Abstract: Recent trends suggest that young people in Britain are refraining from engaging in formal political processes. At the same time, they are increasingly expressing support for, and turning toward, a new and diverse range of non‐institutionalized forms of political action in order to actualize their interests. Using Inglehart's ideas on postmaterialism, we consider whether this apparent rejection of mainstream politics in favour of less conventional – and sometimes radical – forms of political action is changing over time in Britain, reflecting fluctuating economic conditions witnessed over the last two decades. We do this by comparing results from surveys of British 18 year olds conducted in 2002 during an era of relative global prosperity, and then in 2011 at the height of the current global crisis. The findings suggest that British young postmaterialists are considerably more likely than materialists to participate in and support both institutionalized and non‐institutionalized forms of political action.